(untitled) - Hồng, Diễm Thúy (Cần Thơ, 2017)
The purposes of this study are two-fold. Firstly, it is aimed at investigating lowersecondary teachers’ beliefs concerning the use of questioning to scaffold students’ reading comprehension in lower secondary schools. Secondly, it explores eachers’ practices of questioning to scaffold students at pre-reading stage.
Keywords: Tiếng Anh,English language; Dạy và học,Study and teaching